Vonoprazan-associated infection: an analysis of the Japanese Adverse Drug Event Report and the FDA Adverse Event Reporting System - Mengling Ouyang; Shupeng Zou; Qian Cheng; Xuan Shi; Yazheng Zhao; Minghui Sun (SAGE Publishing, 2024)
Background: Prolonged or excessive use of acid suppressants may increase the risk of Clostridioides difficile infection (CDI) by altering the intestinal microecosystem. Vonoprazan, a novel potassium-competitive acid blocker, exhibits a faster and more sustained acid-suppressive effect than proton pump inhibitors (PPIs). Therefore, vonoprazan may have a greater impact on the gut microbiota, potentially resulting in CDI. Objectives: This study aimed to explore the potential relationship between acid suppressants and CDI by the Japan Adverse Drug Event Report (JADER) and the FDA Adverse Event Reporting System (FAERS) databases. Design: A retrospective analysis of the JADER and FAERS databases was examined by disproportionality analysis. Methods: We performed signal detection analyses of CDI induced by vonoprazan and PPIs using the JADER and FAERS databases. The association between acid suppressants and CDI was calculated using the reporting odds ratio (ROR) and corresponding 95% confidence interval (95% CI). When the lower limit of the 95% CI is exceeded by 1, the association is considered statistically significant. Results: In the JADER database, the ROR (95% CI) for vonoprazan and PPIs based on suspect drug reports was 15.84 (12.23-20.50) and 2.51 (1.92-3.28), respectively. In the FAERS database, the ROR (95% CI) for vonoprazan and PPIs based on primary and secondary suspect drug reports was 11.50 (6.36-20.82) and 1.42 (1.34-1.51), respectively. Subgroup analysis showed that elderly patients aged 60 years and older were more strongly associated with CDI. The ROR (95% CI) for vonoprazan and PPIs in patients aged 60 years and older in the JADER database was 15.35 (11.59-20.33) and 1.65 (1.14-2.39), respectively. Similarly, the ROR (95% CI) for vonoprazan and PPIs in the FAERS database was 12.56 (6.26-25.20) and 1.43 (1.31-1.57), respectively. Excluding the effect of Helicobacter pylori ( H. pylori ) infection, the use of acid suppressants was still associated with CDI. Conclusion: While signal detection analysis based on the JADER and FAERS databases could not establish causality, our study demonstrated that both vonoprazan and PPIs were significantly associated with CDI. Vonoprazan showed a stronger association with CDI in both databases.